The biology of commercially important fish species and a preliminary assessment of the fisheries potential of Katse Dam, Lesotho - Nthimo, Mokitinyane Francis (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2000)
The construction of the Katse dam was completed in 1996. The dam started filling in 1995 and reached full capacity in early 1998. It forms part of Phase 1A of the Lesotho Highlands Water Project (LHWP). The main aim of the project is to provide revenue to Lesotho, by transferring water from the catchment of the Senqu (Orange) River in Lesotho to South Africa's major industrial and population centres. During the implementation of the project, an estimated 130 people were displaced. However, the most serious impact has been the loss of the traditional way of life in the form of arable and grazing land as a consequence of inundation. One of the obligations of the project is to ensure that the standard of living of those affected by the project is not impaired. The Lesotho Highlands Development Authority identified a number of rural development projects, which included fisheries development. This study is an integral part of fisheries development in Lesotho. The aim of this study was to gain an understanding of the biology and the demographics of the fish species in the lake. This information would serve as the basis for the development of a management plan for the sustainable utilisation of the fisheries resources. To achieve this aim, the following specific objectives were addressed: 1. Investigation of the biology of the three principal species. 2. Description of the key population parameters (growth, mortality & recruitment). 3. Investigation of the distribution and relative abundance of the three species. The three principal species in the Katse dam are rainbow trout, Oncorhynchus mykiss, and the two cyprinids, Barbus aeneus and Labeo capensis. Sectioned otoliths were used to age O. mykiss while both otoliths and scales were used to age B. aeneus and L. capensis. Marginal zone analysis revealed that slow growth was experienced in winter for the three species. The maximum-recorded age for both B. aeneus and L. capensis was 12 years while O. mykiss reached 4 years. There was no significant difference in growth rates of the different sexes and growth was best described by the 3 parameter Von-Bertalanfy growth model as Lt = 603[1-eâ »Â°Â·Â¹â µâ ½t â º Â°Â·Â°Â³â ¾] for B. aeneus, Lt = 526[1-eâ »Â°Â·Â²Â¹â ½t â º Â°Â·â ¹â ¾] for O. mykiss and Lt = 521[1-eâ »Â°Â·Â¹â ·â ½t â º Â°Â·Â²Â¹â ¾] for L.capensis. Male and female O. mykiss attained 50% sexual maturity (Lmâ‚…â‚€) at 235 and 275mm FL, respectively. There was no difference in Lmâ‚…â‚€ for male and female B. aeneus and L. capensis. B. aeneus reached sexual maturity at 285mm FL while L. capensis reached sexual maturity at 244mm. Both cyprinid species spawned in summer (November to January) while O. mykiss spawned in winter (May to August). The mean total mortality rate (Z) estimated from catch curves and Butterworth et al (1989) equation was 0.72 yrâ »Â¹ for B. aeneus, 0.62 yrâ »Â¹ for L. capensis and 1.32 yrâ »Â¹ for O. mykiss. The estimate of natural mortality was 0.41 yrâ »Â¹ for both B. aeneus and L. capensis and 0.81yrâ »Â¹ for O. mykiss.
Keywords: Fishes -- Lesotho -- Katse dam; Fishes -- Physiology; Rainbow trout; Barbus aeneus; Labeo; Katse dam (Lesotho); Fisheries -- Lesotho -- Katse dam; Fishery management -- Lesotho